Pengaturan Penjatuhan Sanksi terhadap Pelanggaran Berat yang Dilakukan oleh Notaris dalam Perspektif Peraturan Perundang-Undangan - Ratih Novitasari; Yetniwati Yetniwati; Dwi Suryahartati (Wajah Hukum, 2022)
Sanction about violations that commited by Notary are regulated in Notary position regulation and ethics code of Notary. But, there is no further explanation regarding the form of violations such as what can be said as a minor violation to a serious violation in the imposition of a Notary sanction cause the  ambiguity of norms in Article 9 paragraph (1) letter d regarding Notary violations and Article 12 letter d regarding gross violations by Notary. The purpose of this study is to find out and analyze the arrangements of sanctions imposition for gross violations committed by Notary and Notary legal efforts that are sanctioned for gross violations in the perspective of laws and regulations by using the type of normative juridical law research. To determine the types of violations or classification of notary violations, based on the review and policy of the Notary Supervisory Assembly as an authorized official with reference to applicable laws and regulations because there is no further explanation of the classification of notary violations. If the Notary feels the objection to being sanctioned for gross violations, then the Notary can file a legal effort that is to file a lawsuit with the State Administrative Court.